Correlation Misperception in Choice - Ellis, Andrew; Piccione, Michele (American Economic Review, 2017)
We present a decision-theoretic analysis of an agent's understanding of the interdependencies in her choices. We provide the foundations for a simple and flexible model that allows the misperception of correlated risks. We introduce a framework in which the decision maker chooses a portfolio of assets among which she may misperceive the joint returns, and present simple axioms equivalent to a representation in which she attaches a probability to each possible joint distribution over returns and then maximizes subjective expected utility using her ( possibly misspecified) beliefs. (JEL D11, D81, D83, G11)